EXPLORING THE EXPERIENCE OF WOMEN LEADERS IN BREAKING GENDER BARRIERS ON ISLAMIC BOARDING SCHOOLS LEADERSHIP IN INDONESIA - Numan, Muhammad; Ghofur, Salsabila Abdul; Mumtaz, Muhammad Fayyaz (Transpublika Publisher, 2024)
This study aimed to explore the experiences of women leaders in breaking gender barriers within the Islamic boarding schools’ leadership in Indonesia. In more specific, this study would identify the factors that have enabled them to overcome the barriers that have traditionally limited the participation of women in leadership roles, specific at this type of Islamic educational institution. A qualitative case study design was employed, and in-depth interviews were conducted with seven participants. The findings revealed that the participants faced a range of barriers, including patriarchal attitudes, lack of access to education, and lack of support from family and community. However, despite these barriers, the participants were able to overcome them and could ‘successfully’ manage to lead the pesantren through utilizing their agency, building networks of support, and most importantly by challenging the patriarchal norms. The findings of this study have important implications for promoting gender equality in Islamic boarding schools and similar patriarchal institutions. This research highlights the need to challenge patriarchal attitudes and policies and to provide women with access to education and support networks. Additionally, this research also emphasizes the need to recognize and address the ways in which different forms of oppression intersect and compound to create unique challenges for marginalized individuals, particularly women leaders in Islamic boarding schools.